Audit Operasional Atas Siklus Pendapatan pada PT New Inti Furnindo Cabang Bandung - Ariyanto, Stefanus; Yanti, Juli (Bina Nusantara University, 2012)
PT New Inti Furnindo Branch Bandung is a private company engaged in the knock-down furniture trade, ,which is a branch of the PT New Inti Furnindo Branch Jakarta. The products sold are produced centrally in Jakarta. The problems faced by this company are annual sales that never meet the targets set by the head quarter, the problems in the organizational structure and procedures of sales and cash receipts that are considered less effective and efficient in achieving corporate objectives. The method used to examine the issue is to do a descriptive analysis to compare the current condition with criteria or standards that should be implemented, examined data relating to the companys revenue cycle and then make direct observations on the implementation of sales procedures, and conduct interviews with officials related to findings. The results indicate that the sales target setting is not effective, the establishment of sales procedures and organizational structures that are inefficient. This condition will cause the company less economies, which in turn affect the companyâs going concern.